ANALISIS KONDISI DAN PENGENDALIAN BAHAYA DI BENGKEL/ LABORATORIUM SEKOLAH MENENGAH KEJURUAN - Hargiyanto, Putut (Jurnal Pendidikan Teknologi dan Kejuruan, 2011)
ABSTRACTThis research aims at revealing (1) types of hazard that potentially arise, (2) the level of existing hazard, (3) the urgency of hazard management that should be done, and (4) the formula of recommended action to control the hazard in workstations or labs. This study belongs to survey research. Data collection techniques were using observation, interview, and visit. The number of workstations or labs were 23 from 11 state schools and 4 private schools. Data validation techniques were obtained through in-depth observation and examniation towards the documentation of visit photos as well as in-depth interview. Data analysis techniques were using quantitative data analysis by calculating the frequency of occurence on each type of hazard and then formulating the average and the percentage. The findings showed that (1) the hazard covered 9 items related to: material handling, the use of hands tool, machine protection, workplace design, lightning, weather, managemnent of noise hazard, vibration and electricity, workers’ facility, and working organization; (2) the average of hazard ratio consisted of (a) 68 cases of non-hazard catagory (58%); (b) 43 cases that required treatment (34%); 10 cases that catagorized as high-priority treatment; and 6 cases that had no data (4%); (3) the hazard control of high urgency on risky condition through repairment action; (4) recommendation for repairment condition was conducted through several stages, i.e. setting the target, selecting the approach, setting the procedure, and conducting continual evaluation. Keywords: hazard control/ management, types and hazard, workstation or labs in Vocational High Schools